EFFECT OF AAHAR AND VIHAR IN NCDS W.S.R TO MODERN ERA - Rakhecha, *Ankita; Shukla, Sanjay (International Journal of Ayurveda and Pharma Research, 2018)
NCD is medical conditions that is not caused by infectious agent but are caused as a direct result of diet, life style and environmental factors. NCDs can refers to chronic diseases which last for long periods of time and progress slowly such as autoimmune disease, cardiovascular diseases, metabolic diseases and chronic kidney diseases. NCDs are leading cause of death in the world representing 63% of all annual deaths. The major cause of NCD is eating unhealthy foods like food so much sweet, high salt, high fat, other junk food and fruits persevered with chemical fertilizer and drinking excess amount of alcohol. Doing no physical activity have increased working hours, high stress level, are major cause of NCDs.Ayurveda is science of life it is mentioned that the 3 pillars of healthy and long life are proper Aahar, Nidra, Bhrahmcharya of our body. Our diet is an essential factor for the formation of body. Charak says that consuming improper diet in improper way is the main cause of disease this is explained under Ashtaaharvidhivisheshayatan, Viruddhaahar. Use of incompatible food leads to skin disorder, GIT disorder, Diabetes, obesity, hence these should be avoided. Ayurveda imphasizes regulation of Aahar Vihar in the form of Ashtaaharvidhivisheshayatan, Dincharya, Ritucharya. Ayurveda can definitely yield reliable efficacious result when applied to all manner of chronic diseases.